OP0236 RELEVANCE OF BIASED PAR2 INHIBITORS IN REDUCING INFLAMMATION AND CARTILAGE DEGRADATION IN IN VITRO AND IN VIVO MODELS OF RHEUMATOID ARTHRITIS. (2nd June 2020) - Brugat, T.; Rugeri, B.; Hommet, G.; Dumont, A.; Baron, L.; Halter, C.; Sémache, M.; Mancini, A.; Amalric, C.; Giambelluco, M.; Lenne, N.; Sidhoum, M.; et al.
Abstract : Background: Protease-activated receptor-2 (PAR2) is a member of a family of G-protein-coupled receptors involved in multiple physiological mechanisms. Compelling evidences have unravelled the key roles of PAR2 in the pathology of both rheumatoid arthritis (RA) and osteoarthritis (OA) 1 . Indeed, in vitro, in vivo and ex vivo experiments showed that this receptor promotes inflammation, cartilage erosion (and subsequent bone degradation), and pain. However, the signalling pathways involved in these functions are not well understood 2 . This is of importance as some pathways can promote the pathogenesis 3 while others prevent it 4 . We developed a new series of small molecules as novel biased PAR2 inhibitors to treat rheumatic diseases. Objectives: To evaluate the efficacy and mechanism of action of new biased PAR2 inhibitors on cartilage erosion and inflammation. Methods: The potency of compounds to inhibit human PAR2 signalling was evaluated in vitro by FLIPR calcium assay in HEK293 cells. The same assay was used to determine their selectivity over human PAR1 and PAR4 as well as murine versions of PAR2. The effect of several PAR2 inhibitors on 9 signalling pathways (Gi2, GoB, Gz, Gq, G13, G14, G15, B arrestin 2, EPAC) was evaluated by the BRET-based bioSens-All™ technology. In vitro anti-hypertrophic effect was determined by measuring the mRNA level of type II collagen, aggrecan and MMP13 in rat chondrocytes after IL1β stimulation. In vitro anti-inflammatory effect was determined by measuring the secretion of IL6, IL8, IL1β, TNFα and IFNγ by human monocytes. In vivo, the pharmacodynamic of our small molecules was assessed after intravenous and oral administration. Therapeutic efficacy of a compound was then evaluated in a collagen-induced arthritis model in DBA1/J mice. In this model, measures of the arthritis index score, body weight, plasma level of TNFα, IL6, IL8 and IL1β and histological evaluation of cartilage erosion were performed. Results: Our new series of small molecules are potent PAR2 inhibitors (IC50<1nM in calcium assay) with some selectivity over PAR1 and PAR4. Our compounds significantly inhibited PAR2 mediated recruitment of Gz, Gq, G13, G14 and G15. However, surprisingly, these small molecules had no effect on B arrestin 2, EPAC, Gi2 and GoB demonstrating that they are biased inhibitors. The effect of our compounds on PAR2 signalling was clearly different from 3 already existing PAR2 inhibitors described in the literature (I-117, AZ3451 and P2pal-18s). We compared the in vitro anti-hypertrophic effect on chondrocyte and anti-inflammatory effect on monocytes of these compounds to determine the importance of PAR2 signalling pathways in these cellular functions. In vivo, our small molecules had good bioavailability after oral administration of 10mg/kg in mice (clearance = 0.038L/h/kg; T½ = 9.9h; AUC= 162564 ng.h/mL; Cmax = 9005 ng/mL). The in vivo therapeutic efficacy of a biased PAR2 inhibitor in a model of collagen-induced arthritis will be presented. Conclusion: Our results show the potency of biased PAR2 inhibitors to reduce both the inflammation and cartilage erosion in rheumatoid arthritis. They confirm the huge potential of PAR2 as a therapeutic target and unravel the relevance of biased antagonism of this receptor to treat rheumatic diseases. References: [1]McCulloch et al., Frontiers in Endocrinology, 2018; 2 Hollenberg et al., British Journal of Pharmacology, 2014; 3 Sharma et al., Genes and Immunity, 2015; 4 Rayees et al., Cell Reports, 2019 Disclosure of Interests: Thibaut Brugat Employee of: Domain Therapeutics, Baptiste Rugeri Employee of: Domain Therapeutics, Gaël Hommet Employee of: Domain Therapeutics, Alexia Dumont Employee of: Domain Therapeutics, Luc Baron Employee of: Domain Therapeutics, Célia Halter Employee of: Domain Therapeutics, Meriem Sémache Employee of: Domain Therapeutics, Arturo Mancini Employee of: Domain Therapeutics, Camille Amalric Employee of: Domain Therapeutics, Marie Giambelluco Employee of: Domain Therapeutics, Nathalie Lenne Employee of: Domain Therapeutics, Marjorie Sidhoum Employee of: Domain Therapeutics, Christel Franchet Employee of: Domain Therapeutics, Stanislas Mayer Employee of: Domain Therapeutics, Xavier Leroy Employee of: Domain Therapeutics, Stephan Schann Employee of: Domain Therapeutics